ANALISIS POSISI STAKEHOLDERS PROGRAM PENANGGULANGAN TB DI LAPAS KLAS I SEMARANG - Shinta Trinovia Kumalasari; Sutopo Patria Jati; Nikie Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Tuberculosis in Indonesia’s Correctional Institution is not a new case. Semarang Class I Correctional Institution on March 2018 has an excess capacity of 114%, and this condition causes a high risk of TB disease. In 2016 until early 2018 has found 25 cases of TB in this Correctional Institutions, although they have been using DOTS strategy. The success of TB program is influenced by multi factors such as the involvement of the stakeholders. This study aims to mapping the position of stakeholders of TB control in Semarang Class I Correctional Institution. This type of research is qualitative with in-depth interviews. The main informants are Doctor, Monev Officer, and Cadres. The Triangulation informants are TB Wasor, Kasi Perawatan, Head of TB Team, and Prisoner as program targets. Stakeholder positions are reviewed based on attitude, influence and interest. The results shows that all stakeholders support the TB control program in Semarang Class I Correctional Institution and all stakeholders except prisoner who have pasive interest in the program. The influence of stakeholders in the program greatly influences its strategic position, particularly its ability to influence through advocacy and supervision. From all stakeholders, only the Wasor, Kasi Perawatan, and Head of TB Team who have strong influence. The conclusion of this study is the position of Wasor, Kasi Perawatan, and Head of TB Team has a supportive attitude, strong influence and active interest in the position of the